TEACHING ACTION IN EARLY CHILDHOOD EDUCATION: FUNDAMENTALS OF EDUCATIONAL WORK IN THE LIGHT OF THE CULTURAL-HISTORICAL THEORY - Cavalcante, Geovana Nascimento; Moura, Gislaine Franco de; Ignacio, Princielle Souza; Paschoal, Jaqueline Delgado [UNESP] (Univ Estadual Paulista-unesp, Fac Ciencias Letras Assis, 2022)
The teacher's action is decisive for the educational work in childhood, therefore, this study aims to discuss the relationship between the teacher and the elaborated culture, as well as the influence of knowledge in the pedagogical relationship with children from 0 to 5 years old. The human development occurs through a cultural-historical process and the acquisition of knowledge occurs through the interaction of the subject with the environment and with others, reinforcing the need for teacher training as an element for the qualification of the educational work. The methodology used was bibliographic research based on Historical and Dialectical Materialism. The results indicate that Early Childhood Education as a space of systematized knowledge has the purpose of promoting the development of the child through proposals intentionally organized by the teacher. This research, therefore, corroborates the reiteration that teaching is the guiding axis for the development of the maximum human potentialities.
Keywords: Education; Early childhood education; Teachers; Cultural-historical; Human development